2009
DOI: 10.3201/eid1501.080502
|View full text |Cite
|
Sign up to set email alerts
|

Predicting High Risk for Human Hantavirus Infections, Sweden

Abstract: An increased risk for hemorrhagic fever with renal syndrome caused by Puumala hantavirus was forecast for Sweden in 2007. The forecast was based on a predicted increase in the number of Myodes glareolus rodents (reservoir hosts). Despite raised awareness and preparedness, the number of human cases during July 2007–June 2008 was 1,483, a new high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 11 publications
0
77
0
1
Order By: Relevance
“…Of taxonomic groups, rodents are considered one of the largest sources of zoonotic agents (Luis et al 2013). In northern Europe, rodent populations display multiannual, high-amplitude, cyclic density fluctuations (Hansson and Henttonen 1985, Norrdahl 1995, Korpela et al 2013, which can be correlated with the human incidence of zoonotic diseases they spread (for example, Kallio et al 2009, Olsson et al 2009). During density peaks, field voles (Microtus agrestis) become one of the most abundant rodent species in northern Europe (Hanski and Henttonen 1996), yet very little is known of the viruses they carry.…”
Section: Introductionmentioning
confidence: 99%
“…Of taxonomic groups, rodents are considered one of the largest sources of zoonotic agents (Luis et al 2013). In northern Europe, rodent populations display multiannual, high-amplitude, cyclic density fluctuations (Hansson and Henttonen 1985, Norrdahl 1995, Korpela et al 2013, which can be correlated with the human incidence of zoonotic diseases they spread (for example, Kallio et al 2009, Olsson et al 2009). During density peaks, field voles (Microtus agrestis) become one of the most abundant rodent species in northern Europe (Hanski and Henttonen 1996), yet very little is known of the viruses they carry.…”
Section: Introductionmentioning
confidence: 99%
“…However, cyclic NE peaks have also been noted during a 1973-2002 study period, linked to cyclic peaks in local bank vole populations every 2-4 years (mostly 3 years). These "mice years" started with higher reproduction of voles under the snow during winter, and were correlated (R= 0.86) with abundant linden harvest during previous autumn (Olsson et al, 2009). Winter NE peaks are characteristic for Fenno-Scandia, in contrast to the summer peaks in W.-Europe.…”
Section: Russia and Fenno-scandia Two Other Regions In Europe Highlymentioning
confidence: 92%
“…Global warming during wintertime has been incriminated somewhat paradoxically for an increased contact between humans and voles, since the decreased protective snow cover in Fenno-Scandia is supposed to favour bank voles' entry into human dwellings, in search for food and shelter. Overall, the 3-yearly NE peaks in Fenno-Scandia are ascribed to predator-prey cycles, a mechanism very different from the one operative in temperate Europe (Olsson et al, 2009). Indeed, the vegetation type that covers most of Norway, Sweden and Finland is another difference, since the boreal forest or taiga consists mainly of pine trees, in contrast to the temperate forest in the rest of Europe, wherein deciduous broad-leaf trees predominate.…”
Section: Russia and Fenno-scandia Two Other Regions In Europe Highlymentioning
confidence: 99%
See 1 more Smart Citation
“…In line with previous work, we found that most cases were seen in autumn and winter (Table 3). It is also known that the number of reported HFRS cases increase after a hot summer has led to a rich seed season for beech and oak trees (47,48). In the Bartin region, 2008 and 2009 were significantly wetter than previous years, leading to particularly rich seed seasons.…”
Section: Discussionmentioning
confidence: 99%